An Extended Multiple Hardy-Hilbert’s Integral Inequality (Communications in Mathematical Research, 2021)
In this paper, by introducing the norm $∥x∥_α (x ∈ \boldsymbol{R}^n)$, a multiple Hardy-Hilbert's integral inequality with the best constant factor and it's equivalent form aregiven.
Keywords: multiple Hardy-Hilbert's integral inequality; weight function; best constant factor; $β$-function; $Γ$-function.